Preoperative renal dysfunction is a predictor of postoperative atrial fibrillation in coronary artery bypass patients: Predoperativna ledvična disfunkcija je napovedni dejavnik pooperativne atrijske fibrilacije pri bolnikih po kirurški revaskularizaciji srca - Antonič, Miha (Acta Medico-Biotechnica, 2021)
Purpose: Atrial fibrillation is the most common arrhythmia following cardiac surgery. An association between preoperative kidney dysfunction and postoperative atrial fibrillation has been previously reported; however, no study has so far investigated the impact of kidney function during cardiopulmonary bypass on the incidence of atrial fibrillation. The aim of this study was to investigate the value of preoperative renal function and urine output during cardiopulmonary bypass as predictors of postoperative atrial fibrillation in patients undergoing elective coronary artery bypass.Methods: This observational retrospective study included 409 patients who underwent elective coronary artery bypass surgery. According to whether or not atrial fibrillation developed postoperatively, the patients were divided into a sinus rhythm group (n = 340) and a new-onset atrial fibrillation group (n = 69). The impact of preoperative (serum creatinine and estimated glomerular filtration rate) and intraoperative (urine output during cardiopulmonary bypass) kidney function on the incidence of new-onset postoperative atrial fibrillation was assessed using univariable and multivariable analyses.Results:Patients with atrial fibrillation were older, and had higher EuroSCORE II and higher preoperative B-type natriuretic peptide levels than patients with sinus rhythm. Preoperative renal function was worse (higher serum creatinine level and lower estimated glomerular filtration rate) in the atrial fibrillation group than in the sinus rhythm group. However, there were no differences between the groups in urine output during cardiopulmonary bypass. Multivariable analysis identified older age, left ventricular ejection fraction ≤30%, and lower preoperative estimated glomerular filtration rate as independent risk factors for new-onset postoperative atrial fibrillation.Conclusion: Preoperative renal function—but not urine output during cardiopulmonary bypass—is a predictor of new-onset postoperative atrial fibrillation in patients undergoing elective coronary artery bypass surgery.
Keywords: atrial fibrilation; acute kidney injury; coronary artery bypass; cardiopulmonary bypass